Rash in systemic lupus erythematosus: prevalence and relation to cutaneous and non-cutaneous disease manifestations. Issue 6 (June 1992) - Wysenbeek, A J; Guedj, D; Amit, M; Weinberger, A
Abstract : Rash is a common cutaneous sign in patients with systemic lupus erythematosus (SLE) but no data regarding its prevalence or relation to disease manifestations are known, possibly due to the fact that it is a common but non-specific sign. Rash was present in 48/81 (59%) patients with SLE. Patients with rash had more cutaneous symptoms and signs, lymphadenopathy, increased levels of antibodies to double stranded DNA and decreased complement levels. They were also receiving a higher dose of prednisone. There was no difference between patients with and without rash with respect to renal or central nervous system disease. Rash did not correlate with the disease activity index and clinical parameters of disease exacerbation.